2005
DOI: 10.1002/jrs.1335
|View full text |Cite
|
Sign up to set email alerts
|

Electronic effects in SERS by liquid water

Abstract: By exploiting the attenuated total reflection (ATR)-Otto configuration, surface-enhanced Raman scattering of water at monocrystalline copper and silver electrodes in 0.1 M Na 2 SO 4 was observed at cathodic electrode potentials with hydrogen evolution at a laser wavelength of 647.1 nm. The proposed enhancement model is based on the condition that the upshift of the Fermi level of the electrode and the absorption of one laser photon allow an electron of the electrode at the Fermi level to reach the lower level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 69 publications
5
40
1
Order By: Relevance
“…Previous studies of imidazole by SERS have shown that this molecule can adsorb onto a metal surface in two different ways: through the unshared pair of electrons on the N (2) atom or through the π‐electrons system of the imidazole ring . Coordination through the N (2) atom leads the molecule to adopt a perpendicular orientation of the aromatic ring plane with respect to the metal surface, as was also observed for other heteroaromatic rings . In the case of imazalil, this type of coordination implies that the vinyl group may also interact with the metal through the π electrons of the C═C double bond.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Previous studies of imidazole by SERS have shown that this molecule can adsorb onto a metal surface in two different ways: through the unshared pair of electrons on the N (2) atom or through the π‐electrons system of the imidazole ring . Coordination through the N (2) atom leads the molecule to adopt a perpendicular orientation of the aromatic ring plane with respect to the metal surface, as was also observed for other heteroaromatic rings . In the case of imazalil, this type of coordination implies that the vinyl group may also interact with the metal through the π electrons of the C═C double bond.…”
Section: Resultsmentioning
confidence: 90%
“…However, interactions of the benzene ring with the metal are not predicted to justify a shift of this band. Alternatively, this intense band may be related to the presence of water molecules in interaction with the metal surface, according to reported SERS spectra of pure water that showed a band at 1,610 cm −1 .…”
Section: Resultsmentioning
confidence: 92%
“…The experimental results of water on rough silver at a negative potential of À1.5 V, given by Chen and Otto, [41] predict an enhancement factor of 4.2 10 6 for the bending vibrational mode and a factor of 7.3 10 4 for the stretching vibrational mode. The same authors indicate that these values increase if the potential becomes more negative.…”
Section: Sers Spectramentioning
confidence: 96%
“…[40,41,56] To model these negative potentials, we performed calculations by using negatively charged clusters. [40,41,56] To model these negative potentials, we performed calculations by using negatively charged clusters.…”
Section: Structures and Adsorption Spectramentioning
confidence: 99%
See 1 more Smart Citation